(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
Breast cancer, a heterogeneous malignancy, is the most common cancer among women globally, with diverse histological types and pathomorphological features influencing prognosis and treatment. This article explores the types and pathomorphological characteristics of breast cancer, focusing on invasive ductal carcinoma (IDC), invasive lobular carcinoma (ILC), ductal carcinoma in situ (DCIS), and rare subtypes, alongside their histopathological patterns, molecular profiles, and clinical implications. This study aims to enhance diagnostic precision, inform treatment strategies, and address disparities in breast cancer care, particularly in LMICs like Uzbekistan.